Developing heat rate and heat capacity measurement instruments of textile waste solution in the textile dyeing process - Putra, Valentinus Galih Vidia; Purnomosari, Endah; Mohamad, Juliany Ningsih (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
Heat rate and heat capacity are widely used to determine the thermal characteristics, especially for wastewater treatment using electro coagulant. This study aimed to determine the value of heat rate and heat capacity of the waste solution in the textile industry, especially in the dyeing waste, by using a microcontroller device. The method for measuring the specific heat capacity and the textile waste solution's heat rate is based on the principle of the first law of Thermodynamics. Temperature measurements were carried out using a digital temperature sensor type DS18B20. In this research, the heat rate and specific heat of the dyeing solution and mineral water used in the textile industry have been studied. This study uses five types of dyeing waste solution as test solutions, namely green waste solution, orange waste solution, blue waste solution, brown waste solution, and mineral water. This experiment's principle is applying Joule's law by using electrical properties with a microcontroller device used to obtain the rise of temperature data each time in real-time every 2 seconds. Based on this research, it can be concluded that the instrument can be used to measure the heat rate and heat capacity of a textile waste solution. Based on this research, we also found that the specific heat of hard water (Hard water is a kind of water with high mineral content, while soft water is water with low mineral content. Apart from calcium and magnesium ions, the cause of hardness can also be other metal ions as well as bicarbonate and sulfate salts) (4.19 ± 0.77) J/ gram ℃ and the specific heat of the four types of waste solution ranged from (3.20 ± 0.72) J/gram ℃ to (6.83 ± 1.71) J/gram ℃ and also it was found that the heat rate of hard water is 0,0471 ℃/s and the heat rate of the four types of waste solution is range from 0,0289 ℃/s to 0,0617 ℃/s.